Application of strategic HR management and global HR management to company performance in Indonesia - Fitriyani, Desy; Erlina, Puji (Institute of Computer Science (IOCS), 2024)
This study uses qualitative methodology to be able to analyze more deeply the relationship between paradigms on Employee Performance, Strategic HR Management, and Global HR Management within the company. How the paradigm espoused by organizations affects how they manage human resources globally, as well as what impact it has on organizational performance within the company. With a better understanding of the role of paradigms in this context, we can understand how organizations can be more effective in achieving their goals through global management of Strategic HR. In addition, this research can also develop knowledge and insights in learning more about Company Performance, Strategic HR Management, and Global HR Management. This research teaches how employees evaluate their performance. The objectives of this study are: 1) To be able to find out Employee Performance in the company environment. 2) To be able to know the relationship between Company Performance, Strategic HR Management, and Global HR Management.